2021
DOI: 10.3389/fpsyg.2021.644653
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in the Russian Secondary School: Predictive Analysis of Victimization

Abstract: Background: Bullying has been recognized as an important risk factor for personal development in adolescence. Although numerous studies report high prevalence of bullying in Russian schools, limited research was based on the large-scale, nationally representative analysis, which highlights the lack of findings applicable to the national context.Objective: This study aims to address the following research questions: (1) What is the bullying victimization prevalence in Russian secondary schools? (2) What is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
1
0
1
Order By: Relevance
“…It is noteworthy that the Russian Federation and India presented the highest prevalence. Regarding the Russian Federation, representative data from the literature showed that 16% of children were victims of bullying in Russian high schools and that victims tended to avoid reporting these situations of aggression [83]. An increase in domestic violence as a result of COVID-19 [84], especially in middle-low-income countries due to significant structural violence [35,36], could explain the prevalence values found in this study.…”
Section: Discussionsupporting
confidence: 47%
“…It is noteworthy that the Russian Federation and India presented the highest prevalence. Regarding the Russian Federation, representative data from the literature showed that 16% of children were victims of bullying in Russian high schools and that victims tended to avoid reporting these situations of aggression [83]. An increase in domestic violence as a result of COVID-19 [84], especially in middle-low-income countries due to significant structural violence [35,36], could explain the prevalence values found in this study.…”
Section: Discussionsupporting
confidence: 47%
“…The present study is based on the large data set collected in Russian secondary schools. According to the results of several representative surveys, the prevalence of bullying in Russian secondary schools is 13–16% ( Inchley et al, 2020 ; Avanesian et al, 2021 ; Ivaniushina et al, 2021 ). The Health Behavior in School-Aged Children (HBSC), a WHO cross-national study, reports that in 2018 rates of bullying in European countries varied from 3 to 29%, with all-country average 10% ( Inchley et al, 2020 ).…”
Section: The Present Studymentioning
confidence: 99%
“…Хотелось бы отметить также следующее. Как можно заметить, это не первая попытка российских ученых учитывать результаты международных исследований, проведенных на большой группе людей (Артёмов, Пинкевич, 2020;Донцов и др., 2019;Avanesian et al, 2021), в том числе Всемирного обзора ценностей.…”
Section: заключениеunclassified